Pemberantasan Buta Aksara dalam Meningkatkan Pengetahuan Warga - Muhammad Syahrul Kahar ,; Achmad Rusdi,; Nur Hidaya, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The aims of this activity was to know the attachment of people's understanding through learning in order to eradicate illiteracy and identify the results of the illiteracy settlement in sausapor district of Jokte village that has been implemented. The activity was held from August to September 2020 with a sample of 17 learning People, where the data retrieval techniques and the data analysis were carried out using learning observation methods, learning outcomes, interviews and documentation. The results showed that there was a significant improvement by the learning community during the learning process in various aspects including an average reading ability of 76.69, writing ability of 82.87, and counting ability of 65.32. Therefore, there needs to be an ongoing learning process on various learning approaches for each age level that has an impact on improving the social prosperity of the community